CsPbBr3‐Quantum‐Dots/Polystyrene@Silica Hybrid Microsphere Structures with Significantly Improved Stability for White LEDs. Issue 13 (6th May 2019) - Yang, Weiqiang; Gao, Fei; Qiu, Yue; Liu, Weizhen; Xu, Haiyang; Yang, Lili; Liu, Yichun
Abstract: Cesium‐lead‐halide perovskite quantum dots (PQDs), which have superior optical and electronic properties, are regarded as excellent materials for various optoelectronic devices. However, their unstable nature greatly hinders their practical application. Herein, a simple hydrolysis encapsulation method is developed to embed PQDs into mesoporous polystyrene microspheres (MPMs) followed by a silica shell covering process, which generates luminescent PQDs/MPMs@SiO2 hybrid microspheres with significantly enhanced stability. The obtained CsPbBr3 ‐PQDs/MPMs@SiO2 hybrid microspheres show a high photoluminescence quantum yield of 84%. More importantly, the MPMs@silica protective shells effectively cut off direct contact between outer erosive species and the inner embedded PQDs and modify the hybrid microspheres with ultralong alkyl chains for improved resistance to solvents and heat. Hence, these CsPbBr3 ‐PQDs/MPMs@SiO2 hybrid microspheres exhibit good chemical/physical stabilities, even when exposed to harsh environments, such as deionized water, isopropanol, acid/alkali solution, anion‐exchange reactions, and heating. Particularly, the water stability, which produced the remaining ≈48% proportion of the initial fluorescence intensity after a quite long aqueous storage period of 30 d, is the best reported among the stability‐related studies of PQDs. Meanwhile, white light‐emitting diodes (LEDs) are achieved by mixing green CsPbBr3 ‐PQDs/MPMs@SiO2 microspheres with red commercial phosphors on a blue chip. High power efficiency of 81 lm W −1 and good electroluminescence stability are obtained. Abstract : Hybrid microspheres of CsPbBr3 perovskite quantum dots (PQDs)/mesoporous polystyrene microspheres (MPMs)@SiO2, with high photoluminescence quantum yield of 84% and significantly enhanced stability, are synthesized via a hydrolysis‐encapsulation strategy. Enhanced chemical/physical stabilities make these CsPbX3 PQDs suitable for applications even in harsh environments. A white light‐emitting diode (LED) is fabricated based on these fluorescent microspheres, demonstrating a high power efficiency and good working stability.